Customizable Induction Heating Profiles: from Tailored Colloidally Stable Nanoparticles Toward Multi-Stage Heatable Supraparticles - Luthardt, Leoni; Raczka, Theodor; Hurle, Katrin; Müssig, Stephan; Mandel, Karl (Advanced Functional Materials, 2024)

Modulating the Microenvironment of Coumarin Dyes within Multihierarchical Supraparticles: En Route toward Versatile Luminescent Dual-Threshold Temperature Indicators with Ratiometric Readout - Reichstein, Jakob; Luthardt, Leoni; Martello, Valentino Gabriel; Pianetti, Andrea; Wintzheimer, Susanne; Mandel, Karl (Advanced Optical Materials, 2024)
Temperature indicators trace (un)desired thermal impacts across their thermal history upon readout at every point of interest via defined irreversible signal changes. Ratiometric luminescent temperature indicators are attractive due to their fast, sensitive, contactless, spatially-resolved, and self-referenced readout. However, they have a limited working range as commonly only one specific temperature-induced physicochemical effect is exploited. Herein, dual-threshold temperature indicator supraparticles (SPs) are introduced that expand the working range of individual luminescent probes and enhance the extractable information on the thermal history. These SPs derive their functionality from the synergistic interplay of three spectrally distinguishable luminescent species assembled in one multihierarchical, micrometer-sized particle of hybrid organic-inorganic nature. This engineered nanostructure enables the stepwise modulation of the physicochemical microenvironment of two incorporated coumarin species at programmable threshold temperatures, resulting in distinct changes in their emission. As these changes are based on dye-specific mechanisms that are induced in consecutive temperature regimes, the SPs achieve a scarcely reported broad working range (60–200 °C) with temperature-dependent response times of minutes to seconds. From a broader perspective, the conceptualized SPs pioneer in how multiple individual luminescent probes with different excitation-emission properties and indicator mechanisms are synergistically united in one advanced indicator system by precise material engineering.<br
Keywords: luminescence; nanoparticles; sensors; supraparticles; temperature indicators

Multifunctional, Hybrid Materials Design via Spray-Drying: Much more than Just Drying - Wintzheimer, Susanne; Luthardt, Leoni; Cao, Kiet Le Anh; Imaz, Inhar; Maspoch, Daniel; Ogi, Takashi; Bück, Andreas; Debecker, Damien P.; Faustini, Marco; Mandel, Karl (Advanced Materials, 2023)
Spray-drying is a popular and well-known “drying tool” for engineers. This perspective highlights that, beyond this application, spray-drying is a very interesting and powerful tool for materials chemists to enable the design of multifunctional and hybrid materials. Upon spray-drying, the confined space of a liquid droplet is narrowed down, and its ingredients are forced together upon “falling dry.” As detailed in this article, this enables the following material formation strategies either individually or even in combination: nanoparticles and/or molecules can be assembled; precipitation reactions as well as chemical syntheses can be performed; and templated materials can be designed. Beyond this, fragile moieties can be processed, or “precursor materials” be prepared. Post-treatment of spray-dried objects eventually enables the next level in the design of complex materials. Using spray-drying to design (particulate) materials comes with many advantages—but also with many challenges—all of which are outlined here. It is believed that multifunctional, hybrid materials, made via spray-drying, enable very unique property combinations that are particularly highly promising in myriad applications—of which catalysis, diagnostics, purification, storage, and information are highlighte
Keywords: structure formation; spray-drying; nanoparticle assembly; hybrid materials; supraparticles; chemistry in a droplet; functional materials

Reusable and inductively regenerable magnetic activated carbon for removal of organic micropollutants from secondary wastewater effluents - Drenkova-Tuhtan, Asya; Inskeep, Caleb Stewart; Luthardt, Leoni; Deuso, Sara Li; Ballweg, Thomas; Hanselmann, Doris; Béalu, Zoé; Meyer, Carsten; Schug, Benedikt; Steinmetz, Heidrun; Mandel, Karl (Water Research, 2024)
This work introduces a new sustainable alternative of powdered activated carbon (PAC) - magnetically harvestable and reusable after regeneration via inductive heating - for the adsorptive removal of organic micropollutants (OMP) from secondary wastewater effluents. For this purpose, two commercial PACs - lignite “L” (1187 m2/g) and coconut “C”-based (1524 m2/g) - were modified with magnetic iron oxide following two different synthesis approaches: infiltration (“infiltr”) and surface deposition (“depos”) route. The resulting magnetic powdered activated carbons (mPAC) and their precursor PACs were fully characterized before application. The iron oxide content of the modified “L” and “C” samples was ∼30 % and ∼20 %, respectively. Iron oxide gives the PAC beneficial magnetic properties for easy magnetic separation and simultaneously acts as an inductively heatable agent for the carbon regeneration. The infiltrated samples displayed better inductive heating performance and regeneration than their deposited counterparts. Tests with real wastewater showed fast adsorption kinetics of the organic load following the pseudo-second-order kinetic model. Adsorption isotherms were compliant with the Freundlich isotherm model. Sample “L-infiltr” had the best overall adsorption performance throughout 5 reuse cycles when intermediately inductively regenerated (<3 % drop in organics removal per cycle with intermediate regeneration vs. ∼10 % drop per cycle without regeneration). The treated supernatant was additionally tested for 31 representative organic micropollutants and their transformation products (pharmaceuticals, personal care products, industrial chemicals, etc.), where 26 OMPs had consistently high removal (>85 %) throughout 5 cycles with intermediate regeneration and for 28 OMPs the total adsorption efficiency dropped by <5 % after 5 cycle
Keywords: Magnetic induction Magnetite Organic micropollutants Reusable powdered activated carbon Reversible sorption Wastewater effluents